2011
DOI: 10.4269/ajtmh.2011.11-0027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the North American Lung Fluke Paragonimus kellicotti in Missouri and its Development in Mongolian Gerbils

Abstract: Human paragonimiasis is an emerging disease in Missouri. To characterize local parasites, we examined crayfish from three rivers. Metacercaeriae consistent with Paragonimus kellicotti were detected in 69%, 67%, and 37% of crayfish from the Big Piney, Huzzah, and Black Rivers, respectively. Sequencing of the second internal transcribed spacer and other DNA markers confirmed the species identification and the presence of identical parasite sequences in clinical specimens from two human cases. Mongolian gerbils w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…Molecular phylogenetic studies using mitochondrial or non-coding DNA markers indicate that P. westermani and P. kellicotti are not closely related within the genus Paragonimus. 5,13,14 However, these studies provide little information about cross-reactivity of diagnostic antigens. In the past, worm extracts or e/s antigens from a number of old-world Paragonimus species such as P. westermani, P. heterotremus, and Paragonimus africanus have been used for serological diagnosis of paragonimiasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Molecular phylogenetic studies using mitochondrial or non-coding DNA markers indicate that P. westermani and P. kellicotti are not closely related within the genus Paragonimus. 5,13,14 However, these studies provide little information about cross-reactivity of diagnostic antigens. In the past, worm extracts or e/s antigens from a number of old-world Paragonimus species such as P. westermani, P. heterotremus, and Paragonimus africanus have been used for serological diagnosis of paragonimiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Mongolian gerbils were infected with P. kellicotti metacercariae as previously described. 5 Venous blood was collected from infected Mongolian gerbils at various time points after infection (p.i.). Plasma was separated and preserved at −20 C until use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ITS-2 motifs can be utilized for species identifi cation along with RNA secondary structures. Fischer et al (2011) genetically characterized metacercariae of Paragonimus kellicotti found in cray fi sh from USA using ITS-2 region, ITS-1, 5.8S and 28S rDNA sequences. The ITS-2 sequences from metacercariae of P. kellicotti showed 99 % similarity with GenBank sequences of P. kellicotti along with one bp deletion at site 55 and transversion at site 298.…”
Section: Paragonimidae (Dollfus 1939)mentioning
confidence: 99%